CONDUCTING FUNCTIONAL ANALYSES OF PROBLEM BEHAVIOR VIA TELEHEALTH. Issue 1 (1st April 2013) - Wacker, David P.; Lee, John F.; Dalmau, Yaniz C. Padilla; Kopelman, Todd G.; Lindgren, Scott D.; Kuhle, Jennifer; Pelzel, Kelly E.; Waldron, Debra B.
Abstract Behavior consultants conducted functional analyses (FAs) via telehealth with 20 young children with autism spectrum disorders between the ages of 29 and 80 months who displayed problem behavior and lived an average of 222 miles from the tertiary hospital that housed the behavior consultants. Participants' parents conducted all procedures during weekly telehealth consultations in regional clinics located an average of 15 miles from the participants' homes. Behavior consultants briefly trained parent assistants to provide on‐site support for families during consultations. FAs completed within a multielement design identified environmental variables that maintained problem behavior for 18 of the 20 cases, and interrater agreement averaged over 90%. Results suggested that behavior analysts can conduct FAs effectively and efficiently via telehealth.